Studi Komparatif Pola Rekrutmen Bacaleg Perempuan PPP dan PAN di Kota Tangerang - Zidan Hizbullah (Universitas Warmadewa, 2023)
This research aims to examine the political recruitment process carried out by two Islamic Nationalist Parties in recruiting female Bacaleg in the 2019 Legislative Election in Tangerang City. The discussion regarding women's participation in political contestation is still an interesting issue because the political world is believed to be a realm that is thick with patriarchal culture, so it often causes unfair treatment received by women when they try to attend through political recruitment activities organized by political parties. Hazan and Rahat's theory of political party organizing related to political recruitment was used to dissect the field findings. This study uses qualitative research methods descriptive case study approach with comparative structure. The result of this study is that PPP and PAN in recruiting female candidates apply the same pattern, which tends to lead to exclusivity and its implementation is in accordance with Article 29 paragraph (2) of Law Number 2 of 2011 concerning Political Parties, because these two parties carry out political recruitment openly. The reason for the lack of women occupying numbers 1 and 2 is due to the lack of value weight from women which affects the process of assigning sequence numbers for candidates.